Analysis technique for ultra shallow junction using medium energy ion scattering time‐of‐flight elastic recoil detection analysis. (11th June 2014) - Abo, Satoshi; Pei, Ri; Yuan, Yao Xin; Wakaya, Fujio; Takai, Mikio; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> An analysis technique for an ultra shallow junction in shrunk semiconductor devices was developed using medium energy ion scattering (MEIS) time‐of‐flight (TOF) elastic recoil detection analysis (ERDA). The energy of the recoiled and forward‐scattered ions was analyzed using a toroidal electrostatic analyzer with an energy resolution of less than 0.4 keV in MEIS‐ERDA. TOF was used for a mass separation in MEIS‐ERDA with high energy resolution, because an energy resolution of conventional ERDA with an absorber foil was degraded by the energy loss straggling on the foil. The probe beam of 100‐keV N+ was chopped by a function generator for the TOF measurement. Three standard samples of 2‐keV B+ implanted Si with doses of 0.5, 1.0, and 1.5 × 1016/cm2 were measured using MEIS‐TOF‐ERDA. The measured depth profile of the B+ implanted Si sample with a dose of 0.5 × 1016/cm2 was in good agreement with the simulated profile. The projected range and its straggling of 2‐keV B+ implantation into a Si substrate measured using MEIS‐TOF‐ERDA were 6.3 and 6.1 nm, respectively. The results indicated that an ultra shallow junction fabricated by low energy and light ion implantation can be analyzed using developed MEIS‐TOF‐ERDA. Copyright © 2014 John Wiley & Sons, Ltd.